Improving Students' IPAS Interest and Learning Outcomes Through Audio-Visual Aided Contextual Teaching - Herlina Septikarini; Sudarmiani Sudarmiani; Yudi Hartono (CV. Edujavare Publishing, 2026)
Traditional teacher-centered instruction often results in low student engagement and poor academic performance in elementary science and social studies (IPAS). This study aims to describe the implementation of the Audio-Visual aided Contextual Teaching and Learning (CTL) model and evaluate its effectiveness in improving student interest and learning outcomes at SDN Gedangsewu 1. The research employed a Classroom Action Research (PTK) design consisting of two cycles involving 24 fifth-grade students. Data were gathered through observation checklists for student interest and written tests for learning achievement, analyzed using descriptive statistics. Findings revealed a significant increase in student interest, which rose from a baseline of 42.3% to 62.5% in Cycle I and reached 80.6% in Cycle II. Correspondingly, the class average for learning outcomes improved from 59.8 to 83.8, with classical completeness achieving 100% by the end of the second cycle. The results indicate that the integration of audio-visual media within a contextual framework effectively fosters a meaningful learning environment, successfully enhancing both student motivation and cognitive achievement in IPAS. This model is recommended for teachers seeking to make abstract concepts more concrete and relevant for elementary students.